"Rather Active Today than Radioactive Tomorrow!" Environmental Justice and the Anti-Nuclear Movement in 1970s Wyhl, West Germany. (1st January 2012) - Kalb, Martin
Abstract : This article applies new understandings of environmental justice theory to a specific local case study. More precisely, it uses a broader conception of environmental justice theory to further our understanding of the rise of the German anti-nuclear movement. After briefly introducing new trends within environmental justice theory that move beyond equity, the article applies this framework to the German context. It thereby helps define Umweltgerechtigkeit or environmental justice in Germany, and then applies this nuanced framework to the events in Wyhl, a small community on the forefront against nuclear power in the early 1970s. The article ultimately argues that environmental justice needs to move beyond focusing on the unequal distribution of environmental goods and bads. It also indicates that environmental justice is an excellent historical lens and a powerful interdisciplinary framework that can provide unique avenues for revisiting existing scholarship.